Insight into the RNA Exosome Complex Through Modeling Pontocerebellar Hypoplasia Type 1b Disease Mutations in Yeast. Issue 1 (1st January 2017) - Fasken, Milo B; Losh, Jillian S; Leung, Sara W; Brutus, Sergine; Avin, Brittany; Vaught, Jillian C; Potter-Birriel, Jennifer; Craig, Taylor; Conn, Graeme L; Mills-Lujan, Katherine; Corbett, Anita H; van Hoof, Ambro
Abstract: Pontocerebellar hypoplasia type 1b (PCH1b) is an autosomal recessive disorder that causes cerebellar hypoplasia and spinal motor neuron degeneration, leading to mortality in early childhood. PCH1b is caused by mutations in the RNA exosome subunit gene, EXOSC3 . The RNA exosome is an evolutionarily conserved complex, consisting of nine different core subunits, and one or two 3′-5′ exoribonuclease subunits, that mediates several RNA degradation and processing steps. The goal of this study is to assess the functional consequences of the amino acid substitutions that have been identified in EXOSC3 in PCH1b patients. To analyze these EXOSC3 substitutions, we generated the corresponding amino acid substitutions in the Saccharomyces cerevisiae ortholog of EXOSC3, Rrp40 . We find that the rrp40 variants corresponding to EXOSC3-G31A and -D132A do not affect yeast function when expressed as the sole copy of the essential Rrp40 protein. In contrast, the rrp40 -W195R variant, corresponding to EXOSC3-W238R in PCH1b patients, impacts cell growth and RNA exosome function when expressed as the sole copy of Rrp40 . The rrp40 -W195R protein is unstable, and does not associate efficiently with the RNA exosome in cells that also express wild-type Rrp40 . Consistent with these findings in yeast, the levels of mouse EXOSC3 variants are reduced compared to wild-type EXOSC3 in a neuronal cell line. These data suggest that cells possess a mechanism for optimal assembly of functional RNA exosome complex that can discriminate between wild-type and variant exosome subunits. Budding yeast can therefore serve as a useful tool to understand the molecular defects in the RNA exosome caused by PCH1b-associated amino acid substitutions in EXOSC3, and potentially extending to disease-associated substitutions in other exosome subunits.